Perosteal Osteosarcoma of Clavicle - Treated By Limb Salvaging Surgery (Total Cleidectomy) - Ahmed, MU; Basit, MA; Akanda, NI; Hossain, MB; Mukul, HK; Hossain, NM (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2007 Jul;16(2): 214-216The abstract of this article is available on the PubMed website